AKT isoforms have distinct hippocampal expression and roles in synaptic plasticity - Josien Levenga (eLife, 2017)
AKT is a kinase regulating numerous cellular processes in the brain, and mutations in AKT are known to affect brain function. AKT is indirectly implicated in synaptic plasticity, but its direct role has not been studied. Moreover, three highly related AKT isoforms are expressed in the brain, but their individual roles are poorly understood. We find in Mus musculus, each AKT isoform has a unique expression pattern in the hippocampus, with AKT1 and AKT3 primarily in neurons but displaying local differences, while AKT2 is in astrocytes. We also find isoform-specific roles for AKT in multiple paradigms of hippocampal synaptic plasticity in area CA1. AKT1, but not AKT2 or AKT3, is required for L-LTP through regulating activity-induced protein synthesis. Interestingly, AKT activity inhibits mGluR-LTD, with overlapping functions for AKT1 and AKT3. In summary, our studies identify distinct expression patterns and roles in synaptic plasticity for AKT isoforms in the hippocampus.